Abiraterone-induced rhabdomyolysis: A case report. (March 2017) - Moore, Donald C; Moore, Andrew
Abiraterone is an inhibitor of androgen biosynthesis indicated for the treatment of metastatic castration-resistant prostate cancer. Common side effects include diarrhea, edema, hypokalemia, hypertension, and liver function test abnormalities. We report a case of rhabdomyolysis developing in association with the use of abiraterone. Following discontinuation of abiraterone, creatine kinase concentrations decreased gradually throughout the duration of the hospitalization.